Pengembangan Sistem Informasi Badan Pusat Statistik Kabupaten Kuningan Berbasis Android Dengan Metode Prototype - Bacsafra, Marcel Agustine; Kusumawardani, Dwi Mustika; Darmansah, D (STIKOM Tunas Bangsa Pematangsiantar, 2022)
The internet is one proof that information technology is growing. The use of the internet today is increasingly showing trend a positive One of the impacts felt in the development of information technology is a non-departmental government agency of the Central Bureau of Statistics (BPS). BPS is a non-departmental government agency in Indonesia whose main function is to provide statistical data and information. Included in the document analysis results of the BPS data needs survey in 2020, which concludes that consumers in the BPS Integrated Statistics Service (PST) tend to use services that provide data and statistical information in digital or softcopy. This trend is also reinforced by the percentage of the main facility to obtain the largest BPS data is website (41.88%). Therefore, the Kuningan Regency BPS needs to optimize the media for disseminating statistical data and information, one form of innovation that can be done is making an android-based publication application. The application is named Kuningan Dalam Angka Statistik (KUDAMAS). In the development of this application software the prototype and the functionality test uses black box testing. Based on the results of the tests carried out using Black Box testing, the results obtained were successful for all testing of each feature in the application and it can be concluded that the KUDAMAS application has been running according to its function